Students’ propositional logic thinking in higher education from the perspective of disciplines - Fehér, Zoltán; Jaruska, Ladislav; Szarka, Katarína; Tóthová Tarová, Eva (Frontiers in Education, 2023)
Logic and logical thinking are present and play an important role in most of the disciplines at the university level but in different ways. In our research, which has been ongoing for several years, we are investigating the use of propositional logic among university students in different study programmes. Our current study evaluated data from 1429 respondents involving students from 15 universities. The non-standardised knowledge test was previously pilot-tested and consisted of 15 tasks from selected elements of propositional logic in a different natural science subject-specific context. Significant differences in average results were found in terms of students' gender, age, type of secondary school leaving exam and parents' highest education level. Our research mainly aimed to compare students' test scores by students' fields of study. On average, mathematics-informatics students had the highest success rate of 67.4%, compared to students in engineering (61.0%), economics (57.9%), education (56.6%), science (56.5%) and humanities (54.7%). The result is significant (F = 13.521, p-value < 0.001). Furthermore, we found that the students performed differently in three selected areas of formal logic (F = 1108, df = 2, p < 0.001), with the lowest performance on statement negation tasks. The difference in means across groups of tasks is significant by the gender of the students and by their secondary education level.